Die tempel-metafoor in Efesiërs 2:11–22 as deel van identiteitsvorming van die gelowige in-groep - Aletta Vrey (AOSIS, 2021)
The temple metaphor in Ephesians 2:11–22 as part of identity formation of the believing in-group. One of the basic human needs is to belong, feel accepted and be part of a group. During the first century people from different backgrounds believed in Jesus, consequently unity among believers became a challenge. The inclusive heart of God, the atonement of Christ and the Holy Spirit unites believers from different backgrounds and groups. This article examines spiritual unity as part of the believers’ identity as portrayed by the temple metaphor in Ephesians 2:11–22. Christians should acknowledge their differences, as the author of Ephesians clearly does, without causing division in the group. Identity formation is linked to group membership, therefore the identity of the early Christian group is examined, to determine the influence it still has on the present-day unity among believers. We divide our society into groups and tend to discriminate against those that are different from us. These phenomena were part of the social interaction of Christians in the first century. To better understand the social functioning of the ancient Mediterranean world, this article uses Social Identity Theory to identify and compare the groups in Ephesians. The Jews and Gentiles were the out-groups. In the context of the letter, Gentiles were Artemis-worshippers. The Christians formed the in-group. The identity of the out-groups, to which Christians previously belonged, should be considered to determine the identity of the in-group. The metaphor of the spiritual temple identifies believers as becoming part of the temple at the time of their conversion. Unlike the Jewish temple and the temple of Artemis, which were physical buildings with exclusive membership, the temple of the Holy Spirit is an inclusive unity of believers. The Jewish temple was part of the identity of the Jews, the Artemis temple gave identity to the city of Ephesus and the spiritual temple identifies the unity of the Christian in-group. The Christian-identity, whether in the first century or in contemporary society, is unifying and inclusive regardless of our differences. According to the author of Ephesians Christ-founded and Spirit-driven identity should determine Christian thinking and actions.